1993
DOI: 10.1007/bf00376661
|View full text |Cite
|
Sign up to set email alerts
|

Supine and standing sympathovagal balance in athletes and controls

Abstract: Differences in autonomic nerve activity between athletes and controls during supine rest and standing were investigated by recording the cardiac rhythm in 18 professional cyclists and 11 controls. We computed four indexes of autonomic control: the standard deviation (SD) of the interbeat intervals, the coefficient of variance (CV) of the interbeat intervals, the percentage of successive intervals differing by more than 50 ms (pNN50), and the fraction low-frequency (0.07-0.14 Hz) spectral power (LF), and we als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 22 publications
3
18
0
2
Order By: Relevance
“…Lowered LFnu evident in football players would therefore suggest diminished cardiac sympathetic activity. Further players were characterized with lower LF/HF ratio, similar result was reported by Janssen et al [25] in cyclists. The ratio of LF to HF is considered to reflect the sympatho-vagal balance.…”
Section: Discussionsupporting
confidence: 87%
“…Lowered LFnu evident in football players would therefore suggest diminished cardiac sympathetic activity. Further players were characterized with lower LF/HF ratio, similar result was reported by Janssen et al [25] in cyclists. The ratio of LF to HF is considered to reflect the sympatho-vagal balance.…”
Section: Discussionsupporting
confidence: 87%
“…This increase can be achieved in only several weeks of training (Melanson and Freedson 2001). Janssen et al (1993) have found that there is a parasympathetic predominance in athletes in the supine, but not in the standing, position. In the present study, time domain (SD, rMSSD, pNN50) and frequency domain (TP, HF) indexes of parasympathetic activity were increased during both supine and standing, and the same results were observed with Poincare´plot parameters (i.e.…”
Section: Effect Of Endurance Training On Hrvmentioning
confidence: 93%
“…Indeed, increased HRV values, particularly indexes of parasympathetic activity, have been observed in highly trained subjects compared to their healthy sedentary counterparts (Dixon et al 1992;Janssen et al 1993;Macor et al 1996). This increase can be achieved in only several weeks of training (Melanson and Freedson 2001).…”
Section: Effect Of Endurance Training On Hrvmentioning
confidence: 95%
See 1 more Smart Citation
“…Some studies suggest that individuals with better physical fitness present higher HRV at rest (25) . Corroborating this statement, Dixonet al and Janssen et al (8,30) verified that trained individuals, when being compared with untrained individuals, present higher HRV during rest. Thus, the fact the SCI group is composed of wheelchair athletes may explain the reason why the SD1 values at rest were similar to the ones found in the other groups.…”
Section: Discussionmentioning
confidence: 88%